Impact of Ramadan Fasting on Sports Performance - OuYang, Liao; Du, Guangyou; Chi, Zhou; Wu, Zhengkang (Journal of Modern Social Sciences, 2025)
This study systematically reviews and analyzes the impact of Ramadan fasting on athletes' anaerobic performance, aerobic endurance, and strength variations. As a unique form of intermittent fasting with religious and cultural significance, Ramadan fasting requires abstaining from food and drink from sunrise to sunset for an entire month. The study explores the physiological adaptations during fasting, such as changes in energy metabolism, hydration status, and recovery processes, as well as psychological factors like motivation, focus, and perceived exertion that may influence athletic performance. The results indicate that while the effects of Ramadan fasting on anaerobic and aerobic performance are limited, certain performance metrics (e.g., endurance and strength) may improve with proper training and nutrition management. The study emphasizes the importance of maintaining consistent training, optimizing hydration and energy intake during non-fasting hours, and ensuring adequate sleep and recovery. This work provides valuable insights for athletes, coaches, and sports scientists, supporting the development of individualized training and nutrition strategies to help athletes maintain competitive performance while respecting religious and cultural practices. It also offers directions for future research into the long-term effects of Ramadan fasting on athletic performance and the development of evidence-based guidelines.
Keywords: Ramadan fasting; aerobic exercise; anaerobic exercise; endurance exercise